Immune cells and immune cell-targeted therapy in chronic pancreatitis - Zhang, Yu; Zhang, Wen-Qing; Liu, Xin-Yuan; Zhang, Qi; Mao, Tao; Li, Xiao-Yu (Frontiers in Oncology, 2023)
In recent years, studies have attempted to understand the immune cells and mechanisms underlying the pathogenesis of chronic pancreatitis (CP) by constructing a model of CP. Based on these studies, the innate immune response is a key factor in disease pathogenesis and inflammation severity. Novel mechanisms of crosstalk between immune and non-immune pancreatic cells, such as pancreatic stellate cells (PSC), have also been explored. Immune cells, immune responses, and signaling pathways in CP are important factors in the development and progression of pancreatitis. Based on these mechanisms, targeted therapy may provide a feasible scheme to stop or reverse the progression of the disease in the future and provide a new direction for the treatment of CP. This review summarizes the recent advances in research on immune mechanisms in CP and the new advances in treatment based on these mechanisms.